2015
DOI: 10.1093/brain/awv332
|View full text |Cite
|
Sign up to set email alerts
|

Axial myopathy: an overlooked feature of muscle diseases

Abstract: Classically, myopathies are categorized according to limb or cranial nerve muscle affection, but with the growing use of magnetic resonance imaging it has become evident that many well-known myopathies have significant involvement of the axial musculature. New disease entities with selective axial muscle involvement have also been described recently, but overall the axial myopathy is unexplored. We performed a PubMed search using the search terms 'myopathy', 'paraspinal', 'axial' and 'erector'. Axial myopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 77 publications
2
46
0
Order By: Relevance
“…Isolated paraspinal weakness is rare, although it can be found in other myopathies such as sporadic late onset nemaline myopathy, Pompe disease, McArdle disease, facioscapulohumeral muscular dystrophy, or myopathies produced by mutations in the dysferlin, selenoprotein, or RYR-1 genes. 8 In recent years, whole-body muscle MRI studies have demonstrated subclinical involvement of paraspinal muscles in several muscular dystrophies. 9 Muscle biopsy findings in our MLS patient did not seem disease-specific.…”
Section: Case Reportmentioning
confidence: 99%
“…Isolated paraspinal weakness is rare, although it can be found in other myopathies such as sporadic late onset nemaline myopathy, Pompe disease, McArdle disease, facioscapulohumeral muscular dystrophy, or myopathies produced by mutations in the dysferlin, selenoprotein, or RYR-1 genes. 8 In recent years, whole-body muscle MRI studies have demonstrated subclinical involvement of paraspinal muscles in several muscular dystrophies. 9 Muscle biopsy findings in our MLS patient did not seem disease-specific.…”
Section: Case Reportmentioning
confidence: 99%
“…In general, paraspinal muscle weakness is associated with a more widespread myopathy. Isolated paraspinal weakness is rare, although it can be found in other myopathies such as sporadic late onset nemaline myopathy, Pompe disease, McArdle disease, facioscapulohumeral muscular dystrophy, or myopathies produced by mutations in the dysferlin, selenoprotein, or RYR‐1 genes . In recent years, whole‐body muscle MRI studies have demonstrated subclinical involvement of paraspinal muscles in several muscular dystrophies…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this combination of muscle involvement in lower and upper limbs composes a constant pattern and represents a signature of NLSD-M in all stages of the disease. In the clinical context, muscle MRI may help to recognize NLSD-M among different conditions affecting predominantly proximal upper limbs with neck extensor weakness (''man in the barrel'' or ''dropped head'' syndromes) [31][32][33][34] or among different metabolic myopathies, notably those associated with lipidosis on the muscle biopsy [35]. Nevertheless, more muscle imaging data are needed from these other conditions to establish if the ''MRI signature'' in NLSD-M is specific when compared to other muscle lipidosis.…”
Section: Discussionmentioning
confidence: 99%